Do ecosystems have functions? - Ulrich Krohs; Martin Zimmer (Ecology and Evolution, 2023)
Abstract ‘Ecosystem function’ and ‘ecosystem functioning’ became core keywords in the ecological literature on ecosystems, their structure, development and integrity. We investigate functions from the perspective of causal contributions to higher capacities, as selected effects, as contributions to the stability and self‐maintenance of organisms and as type‐fixed effects. Based on an in‐depth discourse in philosophy of science, we conclude that ecosystems do not have functions in any sense that goes beyond a mere description of a causal contribution. We recommend the terms ‘ecosystem function’ and ‘ecosystem functioning’ be avoided in the ecological literature (and beyond).